2007
DOI: 10.1111/j.1460-2466.2007.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Campaign Ads, Online Messaging, and Participation: Extending the Communication Mediation Model

Abstract: Political communication researchers have devoted a great deal of attention to the role of political advertising, the Internet, and political discussion in civic and political life. In this article, we integrate and extend this research by developing a campaign communication mediation model of civic and campaign participation. Two data sets are merged for this inquiry: (a) content-coded ad-buy data on the placement of campaign messages on a market-by-market and program-by-program basis and (b) a national panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
256
1
20

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(290 citation statements)
references
References 36 publications
13
256
1
20
Order By: Relevance
“…Other data sources also contradict the negative effect documented by Gibson et al (2000). These studies find that online political discussion has a significant, positive effect on offline political participation (Hwang, Schmierbach, Paek, Zuniga, & Shah, 2006;Mossberger et al, 2008;Nah, Veenstra, & Shah, 2006;Price, Goldthwaite, Cappella, & Romantan, 2002;Shah et al, 2005;Shah, Cho, et al, 2007). Gibson et al (2000) also include listservs in the online socializing index, but this indicator likely does not explain the negative effects.…”
Section: Resultsmentioning
confidence: 99%
“…Other data sources also contradict the negative effect documented by Gibson et al (2000). These studies find that online political discussion has a significant, positive effect on offline political participation (Hwang, Schmierbach, Paek, Zuniga, & Shah, 2006;Mossberger et al, 2008;Nah, Veenstra, & Shah, 2006;Price, Goldthwaite, Cappella, & Romantan, 2002;Shah et al, 2005;Shah, Cho, et al, 2007). Gibson et al (2000) also include listservs in the online socializing index, but this indicator likely does not explain the negative effects.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the studies of Eveland (2004) and Shah et al (2005) show that information media use enhances political discussion and political efficacy, as well as the competence of people to understand politics, and therefore it enhances political participation. Later, Shah et al (2007) proposed an Orientation-Stimulus-Reasoning-Orientation-Response (O-S-R-O-R) model, an extension of the O-S-O-R model, arguing that the effects of the news media use (S) on political participation (second R) are mediated by reasoning behaviors (first R) and individuals' psychological variables (second O). In other words, the effects of news media use on political participation are achieved by the way of a reasoning process.…”
Section: Media Use Political Attitude and Democratic Valuesmentioning
confidence: 99%
“…Accordingly, based on the framework of the communication mediation model, media use for obtaining news and information stimulates political socialization by shaping attitudes toward democratic values. As an important cognitive variable reflecting a 'personal-psychological' outcome that provides the reasoning process of mental elaboration and collective thinking media use, democratic values, and political participation 391 (Cho et al, 2009;Shah et al, 2007), attitudes toward democratic values can be important in mediating the relationship between media use and political participation.…”
Section: Media Use Political Attitude and Democratic Valuesmentioning
confidence: 99%
“…Previous studies showed that media use contributes to political engagement positively (Jung, Kim, & de Zúñiga, 2011;Schmitt-Beck, 2003;Shah et al, 2007;Sotirovic & McLeod, 2001;Tian, 2011;Willnat, Wong, Tamam, & Annette, 2013). Voting, a typical form of political engagement, requires political information related to whether and how much a certain party or candidate is close to voters' own stances (Downs, 1957).…”
Section: Media Uses and Political Engagementmentioning
confidence: 99%
“…Online media allows people to become involved in social issues or other political things easily and quickly. Individuals and organisations worldwide can get in touch with politicians, parties or any institution, gather information, declare their own opinions, and make contact with others through online media more immediately (Bennett, 2012;de Zúñiga & Valenzuela, 2011;Tolbert & McNeal, 2003;Xenos & Moy, 2007).Previous studies showed that media use contributes to political engagement positively (Jung, Kim, & de Zúñiga, 2011;Schmitt-Beck, 2003;Shah et al, 2007;Sotirovic & McLeod, 2001;Tian, 2011;Willnat, Wong, Tamam, & Annette, 2013). Voting, a typical form of political engagement, requires political information related to whether and how much a certain party or candidate is close to voters' own stances (Downs, 1957).…”
mentioning
confidence: 99%